The Effect of Planting Media Composition and Trichoderma sp. Dosage on the Growth of Cocoa Seedlings (Theobroma cacao L.): Pengaruh Komposisi Media Tanam Dan Dosis Trichoderma Sp. Terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Edrivo Pandapotan Tumanggor; Purwati; Siti Mutmainah (Universitas Widya Gama Mahakam, 2025)
Abstract This study aims to determine the effect of planting media composition and Trichoderma sp. dosage on the growth of cocoa seedlings (Theobroma cacao L.), as well as their interaction. The research was conducted from March to June 2024 at the Agricultural Research Field, Widya Gama Mahakam University, Samarinda. The design used was a factorial randomized block design (RBD) 3 × 4 with three replications. The first factor was planting media composition: P0 (control), P1 (1:1 cattle manure:topsoil), P2 (1:2 cattle manure:topsoil). The second factor was Trichoderma sp. dosage: T0 (control), T1 (20 g/polybag), T2 (30 g/polybag), T3 (40 g/polybag). Parameters observed were number of leaves, plant height, and stem diameter at 30, 60, and 90 DAP. Results showed that P2 and T2 significantly improved cocoa seedling growth. The best interaction was observed in P2T2 for plant height at 90 DAP. Keywords: Cocoa, growing media, cattle manure, Trichoderma sp.